ON FREQUENTLY HYPERCYCLIC C-DISTRIBUTION COSINE FUNCTIONS IN FRECHET SPACES - Kostić, Marko (Matematichki Bilten, 2018)
In this paper, we analyze frequently hypercyclic \(C\)-distribution cosine functions in separable infinite-dimensional complex Fréchet spaces. The notion of frequent hypercyclicity seems to be new even for cosine operator functions in separable infinite-dimensional Banach spaces (real or complex). Our results, formulated also in terms of global fractionally integrated \(C\)-cosine functions, are illustrated with several instructive examples.